Effect of Employee Engagement on Performance of Microfinance Banks in Ilorin Metropolis - Ismaila, Suleiman; Abdulraheem, Issa (African Journal of Stability and Development (AJSD), 2019)
Employee engagement has become an important challenging task for organisations in recent years. Almost all the industries have given proper space to employee engagement but the banking sector has focused on this aspect with greater emphasis as the turnover rate of employees is comparatively high in this sector. The study therefore examined the effect of employee engagement on performance of microfinance banks in Ilorin Metropolis. This study adopted a descriptive research design via the structured online survey instrument-questionnaire. Population of this study includes 232 staff of Microfinance Banks. The study adopted census study owing to the fact that the entire population cannot be reached and studied. The study was analysed using standard multiple regression analysis. The study found that most of the explanatory variables have positive effect on the performance of microfinance banks in Ilorin. The adjusted R2 regression coefficient of profitability is 0.060. Based on the findings, the study concluded that employee engagement indeed has positive effect on organisational performance. Therefore, the study recommended that the profitability of an organisation is brought about if employees are judiciously supervised. The fundamentals of good leadership should therefore be inculcated into the management staff to ensure that the employees are engaged.